Identidade, cultura e segurança alimentar:contradições na produção da quinoa real em comunidades tradicionais de Salinas de Garci de Mendoza, no Altiplano boliviano - Laura, Brigida Choquehuanca (2019)
Since the middle of the twentieth century, the production of “Chenopodium Quinoa Wild” - Quinoa in Bolivia has developed dramatically with incentive policies that allowed the expansion of cultivated crops and created market niches for their commercialization, as an ultra-food with proteins and amino acids but were seen in a pejorative way as “food for the poor or Indians”, so their consumption was reduced to only people from rural and poor areas. However, quinoa has historically been a primary food in the food culture of the indigenous and peasant peoples of the Bolivian Andes. Since the 1980s, quinoa farming has been experiencing drastic changes in producing communities. The first important organization of quinoa producers in the Altiplano was created in 1983, ANAPQUI (National Association of Quinoa Producers), currently a prominent company in the sector which is constantly looking for foreign markets. At this juncture, quinoa became an overvalued food, reaching dynamic markets for peasants and producers who began to depend on this production. In this context, the present dissertation presents and analyzes a reality and scenario experienced in the traditional peasant community - Municipality Salinas de Garci Mendoza (Salinas), from the Altiplano Sul, positioned as the main producer and exporter of the “real quinoa” variety that is uniquely suited to soils salinos, focusing mainly on the changes of this new productive model in the security and food sovereignty of the region and the country. An analytical approach to the risks that causes the production of quinoa in agricultural systems, in the forms of community organization and in the ecosystem systems of the community was also carried out. The results show that quinoa went from a traditional production system to a monoculture and extensive production system where capital and agricultural machinery enter as a new element in the community. The real quinoa as a food that played an important role in the region's food security and sovereignty was weakened, since most of the producers came to produce, exclusively, with the purpose of destining all their production to the market and not for self-consumption. As a total change of productive geography in the plains is contemplated, quinoa was produced on the slope of the mountains with an ancient system of rotation and diversification of crops (potato, canhigua, hollow, fava), which has since disappeared. The pasture of the camelid of the llamas in the mountains was a main source of fertilizer, almost nonexistent today. The intensive production of monocultures from quinoa seriously affects the fauna and wild flora of the community, also in the degradation of soils and the loss of organic matter, which calls into question the extent to which this logic of production in local food security and sovereignty will be viable. The present research tries to contribute with a debate on the theme, from an empirical and real perspective, considering that there is a lack of interest in the academic and social sphere about the striking problems that causes quinoa in the producing communities.